Decellularisation of porcine oesophagu - Lee, Paul Si Yuan (2018)
Esophageal tissue replacement has garnered much interest due to its potential as a new solution for organ failure, and alternatives to implants, transplantation, and reconstructive surgery. As such, the quality of scaffold material is crucial for this tissue engineering construction. This project aims to examine the removal of Sodium Dodecyl Sulphate (SDS) after the perfusion decellularisation of porcine esophagus. DI (de-ionised) water,1% ethanol,5% ethanol is used in this project to remove SDS after decellularising the porcine esophagus. These solutions are used as they are easily accessible and available. In addition, SDS is also soluble in both DI water and ethanol. Ethanol has decellularising properties that can help to further decellularise the porcine esophagus while removing SDS. The decellularisation process begins with the porcine esophagus being perfused using 0.25% SDS at 0.15ml/min. Histology and DNA quantification was conducted to determine the extent of decellularisation of the esophagus. Further perfusion was performed with DI water or 1% ethanol for 24 hours or DI water/1% ethanol/5% ethanol for 72 hours to remove SDS from the decellularised esophagus. The SDS residual liquid samples were collected to determine the SDS concentration using the Biodrop DUO spectrophotometer. The results have shown that DI water is more effective in removing SDS from the decellularised esophagus.